Activated Carbon nanoparticles Loaded with Metformin for Effective Against Hepatocellular Cancer Stem Cells - Sun L; Yao HJ; Li JC; Zhao BQ; Wang YA; Zhang YG (International Journal of Nanomedicine, 2023)
Lan Sun,1 Hong-Juan Yao,2 Jing-Cao Li,1 Bao-Quan Zhao,1 Yong-An Wang,1 Ying-Ge Zhang1 1Key Laboratory of Nanopharmacology and Nanotoxicology, Beijing Institute of Pharmacology and Toxicology, Beijing, People’s Republic of China; 2Key Laboratory of Antibiotic Bioengineering of National Health and Family Planning Commission (NHFPC), Institute of Medicinal Biotechnology (IMB), Chinese Academy of Medical Sciences and Peking Union Medical College (CAMS & PUMC), Beijing, People’s Republic of ChinaCorrespondence: Ying-Ge Zhang; Yong-An Wang, Beijing Institute of Pharmacology and Toxicology, Beijing, People’s Republic of China, Tel +86 10-66930654 ; +86 10-66874607, Fax +86 10-68211656, Email Zhangyg58@126.com; yonganw@126.comIntroduction: Hepatocellular cancer stem cells (CSCs) play crucial roles in hepatocellular cancer initiation, development, relapse, and metastasis. Therefore, eradication of this cell population is a primary objective in hepatocellular cancer therapy. We prepared a nanodrug delivery system with activated carbon nanoparticles (ACNP) as carriers and metformin (MET) as drug (ACNP-MET), which was able to selectively eliminate hepatocellular CSCs and thereby increase the effects of MET on hepatocellular cancers.Methods: ACNP were prepared by ball milling and deposition in distilled water. Suspension of ACNP and MET was mixed and the best ratio of ACNP and MET was determined based on the isothermal adsorption formula. Hepatocellular CSCs were identified as CD133+ cells and cultured in serum-free medium. We investigated the effects of ACNP-MET on hepatocellular CSCs, including the inhibitory effects, the targeting efficiency, self-renewal capacity, and the sphere-forming capacity of hepatocellular CSCs. Next, we evaluated the therapeutic efficacy of ACNP-MET by using in vivo relapsed tumor models of hepatocellular CSCs.Results: The ACNP have a similar size, a regular spherical shape and a smooth surface. The optimal ratio for adsorption was MET: ACNP=1:4. ACNP-MET could target and inhibit the proliferation of CD133+ population and decrease mammosphere formation and renewal of CD133+ population in vitro and in vivo.Conclusion: These results not only suggest that nanodrug delivery system increased the effects of MET, but also shed light on the mechanisms of the therapeutic effects of MET and ACNP-MET on hepatocellular cancers. ACNP, as a good nano-carrier, could strengthen the effect of MET by carrying drugs to the micro-environment of hepatocellular CSCs.Keywords: nanodrug delivery system, metformin, CD133, hepatocellular cancer stem cells